2017
DOI: 10.1038/s41467-017-01822-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Rap1b bound to talin reveals a pathway for triggering integrin activation

Abstract: Activation of transmembrane receptor integrin by talin is essential for inducing cell adhesion. However, the pathway that recruits talin to the membrane, which critically controls talin’s action, remains elusive. Membrane-anchored mammalian small GTPase Rap1 is known to bind talin-F0 domain but the binding was shown to be weak and thus hardly studied. Here we show structurally that talin-F0 binds to human Rap1b like canonical Rap1 effectors despite little sequence homology, and disruption of the binding strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
117
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(132 citation statements)
references
References 57 publications
(79 reference statements)
13
117
2
Order By: Relevance
“…1E). These data implicated talin1 F1 as a second Rap1-binding site important in integrin activation; a surprising conclusion in light of a previous report that the F1 domain does not to bind Rap1b (Zhu et al, 2017).…”
Section: Thd Contains a Second Rap1 Binding Sitesupporting
confidence: 50%
See 3 more Smart Citations
“…1E). These data implicated talin1 F1 as a second Rap1-binding site important in integrin activation; a surprising conclusion in light of a previous report that the F1 domain does not to bind Rap1b (Zhu et al, 2017).…”
Section: Thd Contains a Second Rap1 Binding Sitesupporting
confidence: 50%
“…Furthermore, in Dictyostelium Rap1 directly interacts with the RA domain of talinB (Plak et al, 2016) to enable adhesion during Dictyostelium morphogenesis. Zhu et al confirmed the direct Rap1-talin1 F0 interaction in mammals and showed that membrane-anchored Rap1b in vesicles has enhanced binding to THD, suggesting a mechanism of talin1 recruitment to integrins by Rap1 (Zhu et al, 2017). Quantitative proteomic analyses of murine platelets revealed the high abundance of Rap1b and talin1 (Zeiler et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, the F1 subdomain contains a large (~30aa) unstructured insertion, the F1-loop, which, via a cluster of positively charged residues, interacts with PIP2 and is essential for integrin activation [58]. The F0 subdomain has been shown to bind the membrane-tethered small GTPase, Rap1 [58][59][60] and this interaction has been implicated in membrane targeting of talin to the plasma membrane [59]. Interestingly, the additional F0 subdomain and the F1-loop elements of the talin FERM domain are also found in the kindlin family of proteins [58,61] which synergise with talin to activate integrins [62].…”
Section: The Talin Headmentioning
confidence: 99%